Authority Conflict in Relation to the Job Satisfaction of Ontario CAAT's Instructors - Desroches, Jocelyn (Canadian Journal of Higher Education, 1978)
The paper discusses the more interesting findings of a study on "The Concept and the Determinants of Job Satisfaction". The study's sample population was the full-time Community College Instructors in Ontario. The paper focuses on the relative contribution of individual and organizational factors to instructors' job satisfaction, with special emphasis on the apparent presence in the colleges of an "authority conflict syndrome". Policy recommendations to improve the prevailing situation are suggested.